VOLATILE COMPONENTS, MAGMAS, AND CRITICAL FLUIDS IN UPWELLING MANTLE - Wyllie P.J.; Ryabchikov I.D. (My University, 2000)
The phase diagram for lherzolite-CO2-H2O provides a framework for interpreting the distribution of phase assemblages in the upper mantle with various thermal structures, in different tectonic settings. Experiments show that at depths >80 km, the near-solidus partial melts from lherzolite-CO2-H2O are dolomitic, changing through carbonate-silicate liquids with rising temperatures to mafic liquids; vapor, if it coexists, is aqueous. Experimental data from simple systems suggest that a critical end-point (K) occurs on the mantle solidus at an undetermined depth. Isobaric (T-X) phase diagrams for volatile-bearing systems with K elucidate the contrasting phase relationships for lherzolite-CO2-H2O at depths below and above a critical end-point, arbitrarily placed at 250 km. At levels deeper than K, lherzolite can exist with dolomitic melt, aqueous vapor, or with critical fluids varying continuously between these end-members. Analyses of fluids in microinclusions of fibrous diamonds reveal this same range of compositions, supporting the occurrence of a critical end-point. Other evidence from diamonds indicates that the minimum depth for this end-point is 125 km; maximum depth is not constrained. Constructed cross-sections showing diagrammatically the phase fields intersected by upwelling mantle indicate how rising trace melts may influence trace element concentrations within a mantle plume.